Estimation of efficiency of experimental model of optimization of teaching of students of faculty of physical education - S.I. Belykh (Physical Education of Students, 2013)
A purpose of researches is a ground, development and approbation of conception of perfection of education of students of faculty of physical education for providing of their readiness to realization of the personality oriented physical education. 20 teachers of pedagogical university, 20 teachers of department of Olympic and playing types of sport, 20 students4 courses of pedagogical university were polled. 40 students took part in an experiment. It is set that the specially organized elective employments for the sufficient volume of knowledge was formed for the students of city council 3 disciplines (Pedagogical anthropology, Personality oriented physical education, Creative valeology). The problems of the use of innovative technologies are selected in the process of theoretical and practical preparation of students.